Immunization with Live Human Rhinovirus (HRV) 16 Induces Protection in Cotton Rats against HRV14 Infection - Patel, Mira C.; Pletneva, Lioubov M.; Boukhvalova, Marina S.; Vogel, Stefanie N.; Kajon, Adriana E.; Blanco, Jorge C. G. (Frontiers in Microbiology, 2017)
Human rhinoviruses (HRVs) are the main cause of cold-like illnesses, and currently no vaccine or antiviral therapies against HRVs are available to prevent or mitigate HRV infection. There are more than 150 antigenically heterogeneous HRV serotypes, with ∼90 HRVs belonging to major group species A and B. Development of small animal models that are susceptible to infection with major group HRVs would be beneficial for vaccine research. Previously, we showed that the cotton rat (Sigmodon hispidus) is semi-permissive to HRV16 (major group, species HRV-A virus) infection, replicating in the upper and lower respiratory tracts with measurable pathology, mucus production, and expression of inflammatory mediators. Herein, we report that intranasal infection of cotton rats with HRV14 (major group, species HRV-B virus) results in isolation of infectious virus from the nose and lung. Similar to HRV16, intramuscular immunization with live HRV14 induces homologous protection that correlated with high levels of serum neutralizing antibodies. Vaccination and challenge experiments with HRV14 and HRV16 to evaluate the development of cross-protective immunity demonstrate that intramuscular immunization with live HRV16 significantly protects animals against HRV14 challenge. Determination of the immunological mechanisms involved in heterologous protection and further characterization of infection with other major HRV serotypes in the cotton rat could enhance the robustness of the model to define heterotypic relationships between this diverse group of viruses and thereby increase its potential for development of a multi-serotype HRV vaccine.